1989
DOI: 10.1159/000238690
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Miocamycin in Patients with Liver Cirrhosis

Abstract: The pharmacokinetics of miocamycin, a new macrolide antibiotic, was studied in 6 healthy controls and 6 patients with compensated liver cirrhosis. The results indicate that in chronic liver disease the kinetics of the drug is altered. Therefore, a dosage adjustment of miocamycin is recommended when dealing with these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The pharmacokinetics of macrolide antibiotics usually become modified in patients with hepatic failure because the liver is the major route of elimination of these agents (2,6,8,10). Only a few investigators, however, have suggested a dosage modification when erythromycin, josamycin, or miocamycin are administered to patients with hepatic disease (5,9). For macrolides, with special emphasis on the newer semisynthetic derivatives, the extravascular compartment is of greater importance than the central compartment (6,10).…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacokinetics of macrolide antibiotics usually become modified in patients with hepatic failure because the liver is the major route of elimination of these agents (2,6,8,10). Only a few investigators, however, have suggested a dosage modification when erythromycin, josamycin, or miocamycin are administered to patients with hepatic disease (5,9). For macrolides, with special emphasis on the newer semisynthetic derivatives, the extravascular compartment is of greater importance than the central compartment (6,10).…”
Section: Discussionmentioning
confidence: 99%